Narrative Structures and Techniques of Traditional Series in Digital Platform Content: The case of role-playing series in Minecraft - Barahona Martínez, Jaime; Legerén Lago, Beatriz; Govantes Carrasco, Daniel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
In the digital age, online video platforms have revolutionized the way we consume entertainment. YouTube and Twitch, two of the most popular platforms, have undergone significant evolution since their inception, becoming containers for stories and narratives that go beyond simple improvised amateur content. television within the audiovisual content that is consumed by young people on digital platforms such as YouTube or Twitch. The hypothesis is that the foundations and structures for telling stories are maintained, but we want to find out specifically what lasts through the formats.